Uncertainty analysis of an actuator for a shape memory alloy micro-pump with uncertain parameters. (August 2018) - Guerine, Ahmed; Merzouki, Tarek; Hami, Abdelkhalak El; Zineb, Tarak Ben
Highlights: Static response of an actuator for a shape with uncertain parameters. Effect analysis of the uncertain parameters. Static behavior of an actuator using perturbation method. Abstract: In this paper, we propose a method for taking into account uncertainties of a micro-pump system using Shape Memory Alloy (SMA), based on the perturbation method. The proposed method is used to determine the thermo-mechanical response of a system. Comparisons with the mean value reference solution, illustrate the efficiency of the proposed method. The results are discussed in order to investigate the influence of the most influential parameters of the thermomechanical SMA model. The simulation results are obtained by the proposed method for static analysis with uncertainties.The perturbation method results are compared with the mean value reference solution. The results are discussed in order to investigate the influence of the Young's modulus E, the two transformations strain magnitude ɛ t r a c T and ɛ t r a c T F A, the martensite start Ms and austenite finish Af temperatures and the stress reorientation F ε on the static response of a micro-pump system.